EP-553 A Review of feedback for the Surgical department teaching for foundation doctors. (9th August 2022) - Gulnaz, Nadia; Tasleem, Sadia; Siddique, Khurrum
Abstract: Aims: To assess the usefulness of departmental teaching for the foundation doctors. Methods: Teaching sessions are arranged every Friday covering the most common surgical problems and the management steps appropriate for their level. A feedback questionnaire was sent out to the foundation doctors at the end of their rotation and the data was analyzed for the period of August 2020 to November 2020. Results: The feedback completion rate was 93%. 18 sessions were planned 14 of which went ahead. 1 session was canceled due to junior doctors shortage. Maximum attendees in any session were 10/14 (mean 7) Almost all of them found these sessions useful to and agreed to recommend attending (6–10 on Likert score of 0–10) 75% rated these sessions as "excellent" and all the rest as "very good". 76% showed satisfaction with the time and space allocation. 84% agreed that the session length of 1 hour was adequate. 91% were happy with the adequacy of communication from the organizer. A vast majority suggested flexibility in session timings and relief from ward jobs for improved attendance. Conclusion: Overall Positive Response. Most suggested the timings/ days be changed. The topics covered were appropriate for their level and helped them in their daily practice. Interactive and simulations sessions were the most appreciated ones. Some necessary changes to rota were suggested in order to make these sessions more accessible and useful.